TINJAUAN YURIDIS PERTANGGUNGJAWABAN HUKUM BAGI ANAK SEBAGAI PELAKU PELANGGARAN PASAL 170 AYAT (2) KE-3 KUHP JO UU RI NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DI MARELAN (STUDI PUTUSAN NOMOR: 77/Pid.Sus-Anak/2022/PN Mdn) - Damanik, Micael Jeriko; Paskalena Gea; Ida Mariani Pasaribu (Universitas Sari Mutiara Indonesia, 2025)
Child bullying is a joint act of violence against another person or property, prohibited under criminal law as stipulated in Article 170 of the Indonesian Criminal Code (KUHP). This study aims to investigate how the law is applied to children who commit bullying as regulated in Articles 170 (2) to (3) of the KUHP in conjunction with Law No. 11 of 2012 on the Juvenile Justice System against Decision No:77/Pid.Sus-Anak/2022/PN Mdn, to identify the factors hindering the implementation of the juvenile justice system according to Law No. 11 of 2012, and to determine how parents can supervise their children to prevent bullying. The data analysis method used in this study is qualitative. The results of the legal application decided by the Court in Decision No:77/Pid.Sus-Anak/2022/PN Mdn are in accordance with the elements of criminal acts and juvenile justice laws